Embolization for Hemoptysis—Angiographic Anatomy of Bronchial and Systemic Arteries - Chennur, Vikash Srinivasaiah Setty; Shashi, Kumar Kempegowda; Ryan, Stephen Edward; Hadziomerovic, Adnan; Gupta, Ashish (Journal of Clinical Interventional Radiology ISVIR, 2018)
Massive hemoptysis is a potentially fatal respiratory emergency. The majority of these patients are referred to interventional radiology for bronchial artery embolization (BAE). Immediate clinical success in stopping hemoptysis ranges from 70 to 99%. However, recurrent hemoptysis after BAE is seen in 10 to 55% patients. One of the main reasons for recurrence is incomplete embolization due to unidentified aberrant bronchial and/or non-bronchial systemic arterial supply. This pictorial essay aims to describe the normal and variant bronchial arterial anatomy and non-bronchial systemic arterial feeders to the lungs on conventional angiography; the knowledge of which is critical for interventional radiologists involved in the care of patients with hemoptysis.
Keywords: bronchial; embolization; hemoptysis